DESIGNING MICSTRAW TASK ON GIVING DIRECTION TO SUPPORT TBLT IN TEACHING SPEAKING - Yolanda, Iga; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research was conducted to: formulate the procedures of teaching speaking that the students need in procedure text; design a Micstraw task to encourage  the students to speak about the procedures of how to create something in English; and know the experts’ perceptions whether the design of a Micstraw task is meaningful, interesting and contextual or not to encourage the seventh grade students to speak about the procedures of how to create something in English. This research was carried out at seventh grade students of SMP Negeri 2 Siantan in academic year 2015/2016.This research is a development research which consists of four phases; analyze, design, develop, and evaluate. The need analysis obtained the information that the students need teaching procedures which are meaningful, interesting and contextual in teaching speaking about the procedures of how to create something. The design of a Micstraw task explained the task designing and task developing. The result of evaluation was 3.25 which was categorized as good. It convinced that a Micstraw task is meaningful, interesting and contextual to be used but it still needs little revision.   Keywords: Straw, Procedure Text, Development Research Abstrak: Tujuan penelitian ini adalah untuk: menyusun prosedur mengajar yang siswa butuhkan di dalam materi teks prosedur; merancang a Micstraw task untuk mendorong siswa berbicara tentang prosedur bagaimana membuat sesuatu dalam bahasa inggris; dan mengetahui persepsi para ahli apakah rancangan tugas Micstraw bermakna, menarik dan sesuai konteks atau tidak untuk mendorong siswa kelas VII untuk berbicara tentang prosedur bagaimana membuat sesuatu dalam bahasa inggris. Penelitian ini dilakukan pada siswa kelas VII SMP negeri 2 Siantan tahun akademik 2015/2016. Penelitian ini menggunakan penelitian pengembangan yang terdiri dari empat tahapan; analisis, desain, pengembangan, dan evaluasi. Analisis kebutuhan mengamdung beberapa informasi jika siswa membutuhkan prosedur mengajar yang bermakna, menarik, dan sesuai kontek di dalam mengajarkan berbicara tentang prosedur membuat sesuatu. Desain tugas Micstraw menjelaskan tentang mendesain dan mengembangkan tugas. Hasil evaluasi adalah 3,25 yang dikategorikan baik. Jadi, dapat disimpulkan bahwa tugas Micstraw memiliki prosedur yang  bermakna, menarik, dan sesuai konteks untuk digunakan meskipun masih memerlukan sedikit perbaikan.   Kata Kunci: Sedotan, Teks Prosedur, Penelitian Pengembangan